Brand Image and Customer Loyalty of Parents in a Private Sectarian School in Central Negros - Romatico, Analyn F.; Menes, Carmen C. (Technium Social Sciences Journal, 2025)
Brand image and customer loyalty are critical factors influencing school choice and student retention in today’s competitive education system. Private sectarian institutions build strong brands and lasting stakeholder ties. This study investigated the brand image and customer loyalty of parents at a private sectarian school in Central Negros Occidental. It aimed to examine how demographic factors influence these perceptions and to understand the connection between brand image and loyalty. Ultimately, it sought to inform marketing strategies that enhance stakeholder engagement and institutional growth. This study employed quantitative research design, utilizing a researcher-made questionnaire to gather data on brand image and customer loyalty among parents. The respondents of the study were 145 parents of students who were enrolled in a private sectarian school. Participants were identified through a stratified random sampling technique. Subsequently, the gathered data underwent analysis using both descriptive and inferential statistical methods to determine levels, explore relationships, and identify significant differences related to various demographic factors. The results indicated a strong brand image and high customer loyalty for the private sectarian school across various demographics. However, there are opportunities to enhance perceptions of competence and benefits, particularly among lower-income families. Enhancing these strategies could strengthen the school’s competitiveness and maintain parental loyalty. In addition, the study revealed that a strong brand image significantly influences customer loyalty among parents in a private sectarian school in Central Negros Occidental. Positive perceptions across all brand image dimensions were consistently associated with very high loyalty, regardless of demographic differences. The brand image of the school positively relates to parents’ loyalty. This highlights the importance of strategic branding in strengthening parental commitment and sustaining school enrollment.